Penentuan Kebutuhan Pupuk Kalium untuk Budidaya Tomat Menggunakan Irigasi Tetes dan Mulsa Polyethylene - Amisnaipa, ,; Susila, Anas D.; Situmorang, Rykson; Purnomo, D. Wasgito (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
Tomato var. Ratna was grown with polyethylene mulched and drip irrigation on Inceptisol Dramaga with very low soil K and organic matter during two seasons to K critical concentration, and potassium fertilizer requirement. Experiment used single location approach with three steps of activity.  The first experiment was established in 2004 to develope artificial soil K status by adding K: 0X (0), 1/4X (193.098), 1/2X (386.195), 3/4X (579.293) and X (772.39 kg K2O ha-1), where X was amount of K equal to 772.39 kg K2O ha-1 or 1287.32 kg KCl ha-1.  The second experiment was calibration K study, the experiment arranged in split plot design, with main plot was K status (form first experiment) and sub-plot was K aplication (0, 40, 80, 160, and 320 kg K2O ha-1) in 4 replicated.  Third experiment was optimation of K rate.  The result showed that interval of soil K availability extracted by Morgan Vanema was divided 5  classes,  they were  very low (< 58.25 ppm K), low (58.25-103.25 ppm K), medium (103.25-205.00 ppm K), high (=205 ppm K) and very high (>205.00 ppm K). Potassium recommendation for tomato on Inceptisol with drip irrigation and polyethylene mulch which has very low, low, medium, high and very high K content was 180.20, 131.30 and 82.25 kg K2O ha-1or equal to  300.33, 218.83, and 137.08 KCl ha-1 respectively.   Key words:  Fertilizer, Potassium, calibration,  Lycopersicon esculentum.